A novel NFKB1 agonist remodels tumor microenvironment and activates dendritic cells to promote anti-tumor immunity in colorectal cancer - Ying Chen; Qiaoming Li; Zixiang Wang; Ling V. Sun; Steven X. Hou (Journal of Translational Medicine)
Abstract Background The immunosuppressive nature of the tumor microenvironment (TME) and the existence of cancer stem cells (CSCs) present significant hurdles in tumor therapy. The identification of therapeutic agents that can target both CSCs and the TME could be a potential approach to overcome treatment resistance. Methods We conducted an in vivo chemical screen to identify F1929-1458, which is capable of eliciting an organism-wide response to destroy stem cell tumors in Drosophila. We then performed functional validation using a mouse colorectal cancer graft tumor model established with the CT26 cell line characterized by its high content of CSCs. Single-cell sequencing was employed to analyze alterations in the TME. Small molecule pull-down mass spectrometry, cellular thermal shift assay, drug affinity experiment, and molecular docking were utilized to identify the target of F1929-1458. An in vitro co-culture system was applied to establish that the damage-associated molecular patterns (DAMPs) released by the tumor cells are accountable for the activation of dendritic cells (DCs). Results We demonstrated that F1929-1458 treatment enhanced T cell infiltration and T cell mediated tumor regression, its anti-tumor effect was nullified in nude mice and was abolished after anti-CD3 neutralizing antibody treatment. We found that F1929-1458 binds NFKB1 to activate the NF-κB signaling pathway in tumor cells. The activation further elicits cellular stress, causing tumor cells to release DAMPs (HMGB1-gDNA complex, ATP, and OxLDL). These DAMPs, in turn, stimulate the cGAS-STING and NLRP3 inflammasome pathways in DCs, resulting in the generation of type I IFNs and IL-1β. These cytokines facilitate the maturation of DCs and antigen presentation, ultimately enhancing T cell-mediated anti-tumor immunity. Additionally, we showed that the combination of F1929-1458 and the anti-PD-1 antibody exhibited a synergistic anti-tumor effect. Conclusion Our study identified a novel NFKB1 agonist that promotes anti-tumor immunity by remodeling the TME and activating DCs and that may provide a new way to overcome resistance to current anti-tumor immunotherapy in colorectal cancer.